PENERAPAN LOGIKA FUZZY DENGAN METODE SUGENO UNTUK MENENTUKAN BESARAN KOMISI PADA LAYANAN JASTIP PLGD.STORE - Asrianto, Rudy; Aprianda Effendi (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2022)
Shopping entrusted goods service or most commonly known as jastip (jasa titip) allowing consumen to buy goods through providers of services that are usually different cities or countries. People usualy use this service to purchase goods that are not available in their city, or they have limited acces to the goods. This study aims to determine the amount of commission feee on the PLGD.STORE jastip service by considering the factors that affect the commission on the jastip service. The aplication of Fuzzy Logic in this service is to regulate the ammount of commission fee. The basis fordetermining commission fee is based on the price, the distance and the volume of the product. In this research, we use Sugeno Logic to determine the ammount of the commision fee. The final results of this study are objective with theoretical calculations and are expected to be able to solve the problems in PLGD.STORE and give a win-win solution for both of the jastip service providers and the PLGD.STORE jastip consumers.